Investigating equity and efficiency in carbon pricing with revenue recycling: A combined macro- and micro-modelling approach - Claudia Kettner; Thomas Leoni; Judith Köberl; Dominik Kortschak; Mark Sommer; Veronika Kulmer (Austrian Institute of Economic Research (WIFO), 2024)
While the potential of carbon pricing to curb CO2 emissions is widely acknowledged, the instrument keeps being disputed due to its potential regressivity and the burden it places on low-income households. Recently also the issue of horizontal inequalities has gained in importance in political and scientific discussions, especially with respect to regional differences in the impacts of carbon pricing. We link the macroeconomic model DYNK with the microsimulation model EASI_AT to analyse the effects of carbon pricing under various revenue recycling options, focusing on the regional dimension of the distributional effects of carbon pricing policies. This approach allows combining the detailed household representation of the microsimulation approach with information on the macroeconomic feedback effects. Our results confirm that carbon pricing, without revenue recycling, generally places a higher burden on households living in peripheral regions due to their higher dependence on motorised individual transport, larger dwellings, and a higher prevalence of oil heating systems. However, lump-sum payments targeted at low incomes significantly improve the situation for peripheral regions (the cost of living decreases for 94 percent of households in the lowest income quintile). Ultimately, targeted support (e.g., subsidies for exchanging heating systems) is required to alleviate the burden for low-income households.
Keywords: Q54; Q58; H23; 330; carbon pricing; revenue recycling; distributional impacts; macro-micro-linkage; Austria